Transparent polypropylene medical plastic cup and preparation method thereof

By adding modified nano calcium carbonate and using a twin-screw extruder to the polypropylene to prepare a transparent polypropylene medical plastic cup with high transparency, good mechanical properties, significant antioxidant and antibacterial properties, the problems of poor transparency, insufficient anti-aging performance and poor antibacterial properties of traditional polypropylene materials are solved.

CN119661941AActive Publication Date: 2025-03-21YANCHENG HUIDA BIOTECHNOLOGY CO LTD

Patent Information

Application Number
CN202510186349.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-20
Publication Date
2025-03-21
Estimated Expiration
2045-02-20

AI Technical Summary

Technical Problem

The poor transparency, insufficient anti-aging performance and poor antibacterial performance of traditional polypropylene medical plastic cups limit their application in certain places with high transparency requirements.

Method used

By stirring polypropylene, polyformaldehyde, modified nano-calcium carbonate, kaolin, talc, nucleating agent, lubricant, antioxidant and stabilizer, the mixture is obtained, and melt extrusion, granulation, injection molding is performed in a twin-screw extruder to prepare a transparent polypropylene medical plastic cup.

Benefits of technology

It achieves high transparency, good mechanical properties, significantly improved antioxidant and antibacterial properties of plastic cups, extends the service life of the material, and is suitable for medical devices and food packaging and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of plastic cups, in particular to a transparent polypropylene medical plastic cup and a preparation method thereof. The plastic cup comprises the following components in parts by weight: 60-80 parts of polypropylene, 3-8 parts of polyformaldehyde, 5-15 parts of modified nano calcium carbonate, 3-5 parts of kaolin, 2-4 parts of talcum powder, 0.2-0.4 part of a nucleating agent, 0.5-1.5 parts of a lubricant, 1-3 parts of an antioxidant and 0.5-1.0 part of a stabilizer. The preparation method comprises the following steps: uniformly stirring polypropylene, polyformaldehyde, modified nano calcium carbonate, kaolin, talcum powder, a nucleating agent, a lubricant, an antioxidant and a stabilizer to obtain a mixture; the mixture is subjected to melt extrusion, granulation and injection molding to obtain the plastic cup, and the plastic cup not only has excellent mechanical properties, but also has excellent antibacterial properties, and can effectively prevent growth of bacteria.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of plastic cups, in particular to a transparent polypropylene medical plastic cup and a preparation method thereof. Background Art

[0002] With the continuous advancement of medical technology and the improvement of people's requirements for the quality of medical services, medical plastic products are increasingly used in the medical field. Polypropylene (PP) is a lightweight, high-strength thermoplastic with good mechanical properties, chemical resistance and heat resistance. In addition, polypropylene also has good processing properties and is easy to shape and process into products of various shapes and sizes.

[0003] However, the transparency of traditional polypropylene materials is poor, and the transparency of plastic cups made of polypropylene is poor, which limits its application in some places with high transparency requirements; secondly, because the tertiary carbon atoms contained in the molecular chain structure of polypropylene are very easy to produce thermal oxidation aging degradation and light aging degradation under the conditions of oxygen, heat, and ultraviolet rays, resulting in poor anti-aging performance. In addition, the deficiency of polypropylene in antibacterial also limits its application in the medical field, because the growth of bacteria and microorganisms on the plastic surface may cause cross infection.

[0004] Therefore, we propose a transparent polypropylene medical plastic cup and a preparation method thereof. Summary of the invention

[0005] The object of the present invention is to provide a transparent polypropylene medical plastic cup and a preparation method thereof, so as to solve the problems raised in the prior art.

[0006] To achieve the above object, the present invention provides the following technical solutions: A method for preparing a transparent polypropylene medical plastic cup comprises the following steps: Step S1: mixing polypropylene, polyoxymethylene, modified nano calcium carbonate, kaolin, talcum powder, a nucleating agent, a lubricant, an antioxidant and a stabilizer to obtain a mixture; Step S2: adding the mixed material into a twin-screw extruder for melt extrusion, granulation, and injection molding to obtain a plastic cup.

[0007] Furthermore, the plastic cup comprises the following components by weight: 60-80 parts of polypropylene, 3-8 parts of polyoxymethylene, 5-15 parts of modified nano calcium carbonate, 3-5 parts of kaolin, 2-4 parts of talc, 0.2-0.4 parts of nucleating agent, 0.5-1.5 parts of lubricant, 1-3 parts of antioxidant, and 0.5-1.0 parts of stabilizer.

[0008] Furthermore, the preparation method of the modified nano calcium carbonate is as follows: Step (1): uniformly mix nano calcium carbonate, anhydrous ethanol and deionized water to obtain a mixed solution, adjust the pH value of the system to 9-10, heat to 50-70° C., introduce nitrogen, add vinyl trimethoxysilane, react for 4-6 hours, filter, wash and dry to obtain vinyl nano calcium carbonate; Step (2): uniformly mixing vinyl nano-calcium carbonate and deionized water, adding methyl methacrylate, methacrylamide and modified tea polyphenols, introducing nitrogen, adding potassium persulfate, reacting at 70-80° C. for 10-12 hours, and obtaining an amino compound after centrifugation, washing and drying; Step (3): uniformly mixing the amino compound and the glutaraldehyde aqueous solution, stirring at 25-35° C. for 12-14 hours, centrifuging, washing, and drying to obtain an aldehyde-containing compound; uniformly mixing chitosan and acetic acid solution to obtain a chitosan solution, adding the aldehyde-containing compound and sodium borohydride, reacting at 20-40° C. for 4-6 hours, centrifuging, washing, and drying to obtain an intermediate; Step (4): the intermediate and isopropanol are mixed evenly, sodium hydroxide solution is added to adjust the pH to 9-10, 2,3-epoxypropyltrimethylammonium chloride is added, and the mixture is reacted at 60-70° C. for 5-7 hours. After precipitation, filtration, washing and drying, modified nano-calcium carbonate is obtained.

[0009] In the above technical scheme, the surface of nano-calcium carbonate is modified by vinyltrimethoxysilane to introduce double bonds, and then methyl methacrylate, methacrylamide and modified tea polyphenols are copolymerized and coated on the surface of the nano-calcium carbonate by free radical copolymerization to obtain an amino-containing compound; subsequently, the amino-containing compound and glutaraldehyde are reacted to form a Schiff base bond to obtain an aldehyde-containing compound, and the amino group in chitosan is used to react with the aldehyde group to obtain an intermediate; finally, 2,3-epoxypropyltrimethylammonium chloride (GTA) quaternary ammonium salt is grafted on the C6 hydroxyl group of chitosan to obtain modified nano-calcium carbonate.

[0010] Furthermore, in step (1), the mass ratio of nano-calcium carbonate, anhydrous ethanol, deionized water and vinyltrimethoxysilane is 1:(15-20):(3-5):(2-4).

[0011] Furthermore, in the step (2), the mass ratio of vinyl nano-calcium carbonate to deionized water is 1:(50-100).

[0012] Furthermore, in the step (2), the mass ratio of vinyl nano-calcium carbonate, methyl methacrylate, methacrylamide and modified tea polyphenols is 1: (1-2): (2-4): (0.5-1.5).

[0013] Furthermore, the amount of potassium persulfate used is 1-3% of the total mass of vinyl nano-calcium carbonate, methyl methacrylate, methacrylamide and modified tea polyphenols.

[0014] Furthermore, the preparation method of the modified tea polyphenols is as follows: The tea polyphenols and ethyl acetate are mixed evenly, maleic anhydride and pyridine are added, and the mixture is reacted in a water bath shaker at 50-70° C. for 5-7 hours. After vacuum rotary evaporation, recrystallization and freeze drying, the modified tea polyphenols are obtained.

[0015] Furthermore, the mass ratio of tea polyphenols, ethyl acetate, maleic anhydride and pyridine is 1: (40-50): (0.5-1.0): (0.3-0.5).

[0016] Furthermore, in step (3), the mass ratio of the amino compound to the glutaraldehyde aqueous solution is 1:(50-100), and the concentration of the glutaraldehyde aqueous solution is 25wt%.

[0017] Furthermore, in step (3), the mass ratio of chitosan to acetic acid solution is 1:(25-50), and the concentration of acetic acid solution is 1wt%.

[0018] Furthermore, in step (3), the mass ratio of chitosan, aldehyde-containing compound and sodium borohydride is 1:(0.2-0.6):(0.1-0.2).

[0019] Furthermore, in step (4), the mass ratio of the intermediate, isopropanol and 2,3-epoxypropyltrimethylammonium chloride is 1:(15-30):(3-5), and the concentration of the sodium hydroxide solution is 40wt%.

[0020] Furthermore, the lubricant is polyethylene wax.

[0021] Furthermore, the stabilizer is an organotin stabilizer.

[0022] Furthermore, the temperature of each zone of the twin-screw extruder is: zone 1 178-182°C, zone 2 188-192°C, zone 3 198-202°C, zone 4 208-212°C, zone 5 220-225°C, die head 215-220°C; screw speed 120-180r / min.

[0023] Furthermore, the injection molding adopts an injection molding machine, the screw aspect ratio of the injection molding machine is 12-15, the screw speed is 60-80rpm, the feeding section temperature of the injection molding machine is 200-250℃, the feeding section temperature is 230-260℃, the injection section temperature is 250-280℃, the nozzle temperature is 260-270℃, the mold temperature is 70-80℃, the injection pressure is 70-100Mpa, and the back pressure is 1-2Mp.

[0024] Compared with the prior art, the present invention has the following beneficial effects: 1. A transparent polypropylene medical plastic cup and a preparation method thereof of the present invention uses maleic anhydride as a modifier to prepare modified tea polyphenols, introduces double bonds, and improves its stability. Tea polyphenols, as a natural antioxidant and antibacterial agent, can significantly improve the antioxidant properties of plastics and effectively delay the degradation process of materials caused by oxidation, thereby extending the service life of plastic products. At the same time, the antibacterial properties of tea polyphenols can give polypropylene materials antibacterial functions and reduce the growth of bacteria on the surface of plastics, which is particularly suitable for medical devices, food packaging and other fields that require hygiene.

[0025] 2. A transparent polypropylene medical plastic cup and a preparation method thereof of the present invention, wherein the surface of nano calcium carbonate is further modified by vinyl trimethoxysilane to introduce double bonds, and then methyl methacrylate, methacrylamide and modified tea polyphenols are copolymerized and coated on the surface of nano calcium carbonate by free radical copolymerization to form an organic layer, which is beneficial to improve its compatibility and dispersibility in a polypropylene matrix (PP), reduce agglomeration, and thus improve the mechanical properties, antioxidant and antibacterial properties of the material; Chitosan is a natural biodegradable material with excellent biocompatibility. An aldehyde-containing compound is obtained by reacting an amino compound with glutaraldehyde to form a Schiff base bond. The amino group in chitosan reacts with the aldehyde group to obtain an intermediate. Finally, 2,3-epoxypropyltrimethylammonium chloride (GTA) quaternary ammonium salt is grafted onto the C6 hydroxyl group of chitosan to obtain modified nano-calcium carbonate, which further improves the antibacterial and biocompatibility of the material and extends the service life of the material.

[0026] 3. A transparent polypropylene medical plastic cup and a preparation method thereof of the present invention use polyoxymethylene (POM) as a modifier to enhance the rigidity and toughness of polypropylene (PP), and the POM / PP composite material exhibits good mechanical properties. Modified nano calcium carbonate, kaolin and talcum powder are used as inorganic fillers to effectively improve the mechanical properties of the material, while improving the antioxidant and antibacterial properties of the material, and combining the synergistic effects of nucleating agents, lubricants, antioxidants and stabilizers to obtain a mixture; the mixture is added into a twin-screw extruder for melt extrusion, granulation, and injection molding to obtain a plastic cup, which not only has excellent mechanical properties and transparency, but also has strong antioxidant and antibacterial properties and good thermal stability and processing performance. DETAILED DESCRIPTION

[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] In this embodiment, polypropylene: model is Korea Hyosung R701; polyoxymethylene: brand MC90; nano calcium carbonate: particle size is 20nm, sourced from Shanghai Naio Nano Technology Co., Ltd.; kaolin: calcined kaolin, particle size is 4000 mesh, sourced from Guangdong Yuanlei Powder Co., Ltd.; talcum powder: particle size is 5000 mesh, sourced from Jiangyin Guangyuan Superfine Powder Co., Ltd.; nucleating agent: model is MilladNX8000i; lubricant: polyethylene wax, model is Honeywell AC-6A; antioxidant: model is antioxidant 1010; stabilizer: model TM-181FS.

[0029] In the following examples and comparative examples, 1 part is equal to 10 g.

[0030] Embodiment 1: A method for preparing a transparent polypropylene medical plastic cup, comprising the following process: Step S1: 60 parts of polypropylene, 3 parts of polyoxymethylene, 5 parts of modified nano calcium carbonate, 3 parts of kaolin, 2 parts of talc, 0.2 parts of nucleating agent, 0.5 parts of lubricant, 1 part of antioxidant and 0.5 parts of stabilizer are stirred uniformly to obtain a mixture; Step S2: adding the mixed material into a twin-screw extruder for melt extrusion (the temperature of each zone of the twin-screw extruder is: zone 1 178°C, zone 2 188°C, zone 3 198°C, zone 4 208°C, zone 5 220°C, die head 215°C; screw speed 120r / min), granulation, injection molding using an injection molding machine, the injection molding machine's screw aspect ratio is 12, the screw speed is 60rpm, the injection section temperature of the injection molding machine is 200°C, the feed section temperature is 230°C, the injection section temperature is 250°C, the nozzle temperature is 260°C, the mold temperature is 70°C, the injection pressure is 70Mpa, the back pressure is 1Mp, and after cooling and solidification, the mold is opened to obtain a plastic cup; The preparation method of modified nano calcium carbonate is as follows: Step (1): 5 parts of nano calcium carbonate, 75 parts of anhydrous ethanol and 15 parts of deionized water are mixed uniformly to obtain a mixed solution, the pH of the system is adjusted to 9, the temperature is raised to 50° C., nitrogen is introduced, 10 parts of vinyl trimethoxy silane is added, the reaction is carried out for 4 hours, and after filtering, washing and drying, vinyl nano calcium carbonate is obtained; Step (2): 5 parts of vinyl nano-calcium carbonate and 100 parts of deionized water are mixed evenly, 5 parts of methyl methacrylate, 10 parts of methacrylamide and 2.5 parts of modified tea polyphenols are added, nitrogen is introduced, 0.225 parts of potassium persulfate are added, and the mixture is reacted at 70° C. for 10 hours. After centrifugation, washing and drying, an amino compound is obtained; Step (3): 5 parts of an amino compound and 250 parts of a 25 wt% glutaraldehyde aqueous solution are mixed uniformly, stirred at 25°C for 12 hours, centrifuged, washed, and dried to obtain an aldehyde-containing compound; 25 parts of chitosan and 625 parts of a 1 wt% acetic acid solution are mixed uniformly to obtain a chitosan solution, 5 parts of an aldehyde-containing compound and 0.25 parts of sodium borohydride are added, reacted at 30°C for 5 hours, centrifuged, washed, and dried to obtain an intermediate; Step (4): 5 parts of the intermediate and 75 parts of isopropanol are mixed evenly, 40 wt % sodium hydroxide solution is added to adjust the pH to 9.5, 15 parts of 2,3-epoxypropyltrimethylammonium chloride are added, and the mixture is reacted at 60° C. for 5 h. After precipitation, filtration, washing and drying, modified nano-calcium carbonate is obtained; The preparation method of modified tea polyphenols is as follows: 2.5 parts of tea polyphenols and 100 parts of ethyl acetate were mixed evenly, 1.25 parts of maleic anhydride and 0.75 parts of pyridine were added, and the mixture was reacted on a water bath shaker at 50°C for 5 hours. After vacuum rotary evaporation, recrystallization and freeze-drying, modified tea polyphenols were obtained.

[0031] Embodiment 2: A method for preparing a transparent polypropylene medical plastic cup, comprising the following process: Step S1: 70 parts of polypropylene, 5 parts of polyoxymethylene, 10 parts of modified nano calcium carbonate, 4 parts of kaolin, 3 parts of talc, 0.3 parts of nucleating agent, 1 part of lubricant, 2 parts of antioxidant and 0.8 parts of stabilizer are stirred uniformly to obtain a mixture; Step S2: adding the mixed material into a twin-screw extruder for melt extrusion (the temperature of each zone of the twin-screw extruder is: zone 1 180°C, zone 2 190°C, zone 3 200°C, zone 4 210°C, zone 5 223°C, die head 218°C; screw speed 160r / min), granulation, injection molding using an injection molding machine, the injection molding machine's screw aspect ratio is 14, the screw speed is 70rpm, the injection section temperature of the injection molding machine is 230°C, the feed section temperature is 250°C, the injection section temperature is 260°C, the nozzle temperature is 265°C, the mold temperature is 75°C, the injection pressure is 80Mpa, the back pressure is 1.5Mp, and after cooling and solidification, the mold is opened to obtain a plastic cup; The preparation method of modified nano calcium carbonate is as follows: Step (1): 10 parts of nano calcium carbonate, 180 parts of anhydrous ethanol and 40 parts of deionized water are mixed uniformly to obtain a mixed solution, the pH of the system is adjusted to 9.5, the temperature is raised to 60° C., nitrogen is introduced, 30 parts of vinyl trimethoxy silane is added, the reaction is carried out for 5 hours, and after filtering, washing and drying, vinyl nano calcium carbonate is obtained; Step (2): 10 parts of vinyl nano-calcium carbonate and 800 parts of deionized water are mixed evenly, 15 parts of methyl methacrylate, 30 parts of methacrylamide and 10 parts of modified tea polyphenols are added, nitrogen is introduced, 1.3 parts of potassium persulfate are added, and the mixture is reacted at 75° C. for 11 hours. After centrifugation, washing and drying, an amino compound is obtained; Step (3): uniformly mixing 10 parts of an amino compound and 800 parts of a 25 wt% glutaraldehyde aqueous solution, stirring at 30°C for 13 hours, centrifuging, washing, and drying to obtain an aldehyde-containing compound; uniformly mixing 20 parts of chitosan and 800 parts of a 1 wt% acetic acid solution to obtain a chitosan solution, adding 10 parts of an aldehyde-containing compound and 3 parts of sodium borohydride, reacting at 30°C for 5 hours, centrifuging, washing, and drying to obtain an intermediate; Step (4): 10 parts of the intermediate and 200 parts of isopropanol are mixed evenly, 40 wt% sodium hydroxide solution is added to adjust the pH to 9.5, 40 parts of 2,3-epoxypropyltrimethylammonium chloride are added, and the mixture is reacted at 65° C. for 6 hours. After precipitation, filtration, washing and drying, modified nano-calcium carbonate is obtained; The preparation method of modified tea polyphenols is as follows: 10 parts of tea polyphenols and 450 parts of ethyl acetate were mixed evenly, 8 parts of maleic anhydride and 4 parts of pyridine were added, and the mixture was reacted on a water bath shaker at 60°C for 6 hours. After vacuum rotary evaporation, recrystallization and freeze-drying, modified tea polyphenols were obtained.

[0032] Embodiment 3: A method for preparing a transparent polypropylene medical plastic cup, comprising the following process: Step S1: 80 parts of polypropylene, 8 parts of polyoxymethylene, 15 parts of modified nano calcium carbonate, 5 parts of kaolin, 4 parts of talc, 0.4 parts of nucleating agent, 1.5 parts of lubricant, 3 parts of antioxidant and 1.0 part of stabilizer are stirred uniformly to obtain a mixture; Step S2: adding the mixed material into a twin-screw extruder for melt extrusion (the temperature of each zone of the twin-screw extruder is: zone 1 182°C, zone 2 192°C, zone 3 202°C, zone 4 212°C, zone 5 225°C, die head 220°C; screw speed 180r / min), granulation, injection molding using an injection molding machine, the injection molding machine's screw aspect ratio is 15, the screw speed is 80rpm, the injection section temperature of the injection molding machine is 250°C, the feed section temperature is 260°C, the injection section temperature is 280°C, the nozzle temperature is 270°C, the mold temperature is 80°C, the injection pressure is 100Mpa, the back pressure is 2Mp, and after cooling and solidification, the mold is opened to obtain a plastic cup; The preparation method of modified nano calcium carbonate is as follows: Step (1): 15 parts of nano-calcium carbonate, 300 parts of anhydrous ethanol and 75 parts of deionized water are mixed uniformly to obtain a mixed solution, the pH of the system is adjusted to 10, the temperature is raised to 70° C., nitrogen is introduced, 60 parts of vinyl trimethoxy silane is added, the reaction is carried out for 6 hours, and after filtering, washing and drying, vinyl nano-calcium carbonate is obtained; Step (2): 15 parts of vinyl nano-calcium carbonate and 1500 parts of deionized water are mixed evenly, 30 parts of methyl methacrylate, 60 parts of methacrylamide and 22.5 parts of modified tea polyphenols are added, nitrogen is introduced, potassium persulfate is added, and the mixture is reacted at 80° C. for 12 hours. After centrifugation, washing and drying, an amino compound is obtained; Step (3): 15 parts of an amino compound and 1500 parts of a 25 wt% glutaraldehyde aqueous solution are mixed uniformly, stirred at 35°C for 14 hours, centrifuged, washed, and dried to obtain an aldehyde-containing compound; 25 parts of chitosan and 1250 parts of a 1 wt% acetic acid solution are mixed uniformly to obtain a chitosan solution, 15 parts of an aldehyde-containing compound and 5 parts of sodium borohydride are added, reacted at 40°C for 6 hours, centrifuged, washed, and dried to obtain an intermediate; Step (4): 15 parts of the intermediate and 450 parts of isopropanol are mixed evenly, 40 wt% sodium hydroxide solution is added to adjust the pH to 10, 75 parts of 2,3-epoxypropyltrimethylammonium chloride are added, and the mixture is reacted at 70° C. for 7 h. After precipitation, filtration, washing and drying, modified nano-calcium carbonate is obtained; The preparation method of modified tea polyphenols is as follows: 25 parts of tea polyphenols and 1250 parts of ethyl acetate were mixed evenly, 25 parts of maleic anhydride and 12.5 parts of pyridine were added, and the mixture was reacted on a water bath shaker at 70°C for 7 hours. After vacuum rotary evaporation, recrystallization and freeze-drying, modified tea polyphenols were obtained.

[0033] Comparative Example 1: A method for preparing a transparent polypropylene medical plastic cup, comprising the following processes: Compared with Example 2, in Comparative Example 1, the modified tea polyphenols are replaced with tea polyphenols of the same mass, and the other steps are the same as those of Example 2.

[0034] Comparative Example 2: A method for preparing a transparent polypropylene medical plastic cup, comprising the following processes: Compared with Example 2, the modified nano-calcium carbonate in Comparative Example 2 is replaced with nano-calcium carbonate of the same mass, and the other steps are the same as those in Example 2.

[0035] Comparative Example 3: A method for preparing a transparent polypropylene medical plastic cup, comprising the following processes: Compared with Example 2, Comparative Example 3 does not add polyoxymethylene, and other steps are the same as Example 2.

[0036] Comparative Example 4: A method for preparing a transparent polypropylene medical plastic cup, comprising the following processes: The preparation method of modified nano calcium carbonate is as follows: Step (1): 10 parts of nano calcium carbonate, 180 parts of anhydrous ethanol and 40 parts of deionized water are mixed uniformly to obtain a mixed solution, the pH of the system is adjusted to 9.5, the temperature is raised to 60° C., nitrogen is introduced, 30 parts of vinyl trimethoxy silane is added, the reaction is carried out for 5 hours, and after filtering, washing and drying, vinyl nano calcium carbonate is obtained; Step (2): 10 parts of vinyl nano-calcium carbonate and 800 parts of deionized water are mixed evenly, 15 parts of methyl methacrylate, 30 parts of methacrylamide and 10 parts of modified tea polyphenols are added, nitrogen is introduced, 1.3 parts of potassium persulfate are added, and the mixture is reacted at 75° C. for 11 hours. After centrifugation, washing and drying, an amino compound is obtained; Step (3): uniformly mixing 10 parts of an amino compound and 800 parts of a 25 wt% glutaraldehyde aqueous solution, stirring at 30°C for 13 hours, centrifuging, washing, and drying to obtain an aldehyde-containing compound; uniformly mixing 20 parts of chitosan and 800 parts of a 1 wt% acetic acid solution to obtain a chitosan solution, adding 10 parts of an aldehyde-containing compound and 3 parts of sodium borohydride, reacting at 30°C for 5 hours, centrifuging, washing, and drying to obtain an intermediate; Step (4): 10 parts of the intermediate and 200 parts of isopropanol are mixed evenly, 40 wt % sodium hydroxide solution is added to adjust the pH to 9.5, 10 parts of 2,3-epoxypropyltrimethylammonium chloride are added, and the mixture is reacted at 65° C. for 6 h. After precipitation, filtration, washing and drying, modified nano-calcium carbonate is obtained; Compared with Example 2, in step (4) of Comparative Example 4, the mass ratio of the intermediate to 2,3-epoxypropyltrimethylammonium chloride is 1:1, and the other steps are the same as those of Example 2.

[0037] Experiment: Take the plastic cups obtained in Examples 1-3 and Comparative Examples 1-4, prepare samples, test their properties respectively and record the test results: Tensile performance test: carried out in accordance with GB / T1040.2-2022, tensile rate 50mm / min.

[0038] Xenon lamp aging test: According to GB / T 16422.2-2014, xenon lamp is used as the light source, and the irradiation intensity is 0.51W / m 2 The black mark temperature was cycled between 65°C and 100°C, the exposure period was 102 min drying and 18 min spraying, the test time was 96 h, the tensile strength before and after aging was measured, and the tensile strength retention rate was calculated.

[0039] Antibacterial test: The antibacterial property was tested by plate colony count method. The test strain was Staphylococcus aureus (ATCC6538). The strain was inoculated into sterilized nutrient broth under aseptic conditions and cultured at 37°C for 24 hours to obtain concentrated bacterial solution. The concentrated bacterial solution was inoculated onto nutrient agar plates with an inoculation loop and cultured at 37°C for 24 hours. A single colony with good production was picked and inoculated into nutrient broth medium and cultured for 48 hours under the same conditions. The concentration of the bacterial solution was adjusted to 1×10 9 CFU / L, for later use; make a plastic cup into a sample of 50mm×50mm in size, disinfect it with 75% ethanol and dry it, take 0.2mL of bacterial liquid and drop it on the surface of the sample, cover the surface of the sample with a 0.10mm thick polyethylene film, and culture it in a constant temperature incubator for 24 hours at a temperature of 37°C and a relative humidity of 90%. After 24 hours, elute the bacterial liquid with an eluent, and count the eluent using the plate counting method. Test 3 parallel samples for each group of samples, and take the average value of the results.

[0040] The test results are as follows:

[0041] According to the data in the above table, we can clearly draw the following conclusions: Compared with Examples 1-3, the tensile strength retention rate of the product obtained in Comparative Example 1 decreases, indicating that the present invention improves the reaction activity of tea polyphenols by modifying them, enabling them to effectively coat nano-calcium carbonate, thereby enhancing their anti-aging properties.

[0042] Compared with Examples 1-3, the tensile strength and tensile strength retention rate of the product obtained in Comparative Example 2 are both decreased, indicating that the modified nano-calcium carbonate prepared by the present invention has better compatibility, antioxidant properties and antibacterial properties than the unmodified nano-calcium carbonate; the tensile strength of the product obtained in Comparative Example 3 is decreased, which shows that the addition of polyformaldehyde is beneficial to improving the mechanical properties of the material.

[0043] Compared with Examples 1-3, the antibacterial rate of the product obtained in Comparative Example 4 is reduced. It can be seen that when the amount of 2,3-epoxypropyltrimethylammonium chloride added is reduced, the antibacterial performance of the material will decrease.

[0044] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A method for preparing a transparent polypropylene medical plastic cup, characterized in that: The steps include: Step S1: mixing polypropylene, polyoxymethylene, modified nano calcium carbonate, kaolin, talcum powder, a nucleating agent, a lubricant, an antioxidant and a stabilizer to obtain a mixture; Step S2: adding the mixed material into a twin-screw extruder for melt extrusion, granulation, and injection molding to obtain a plastic cup; The preparation method of the modified nano calcium carbonate is as follows: Step (1): uniformly mix nano calcium carbonate, anhydrous ethanol and deionized water to obtain a mixed solution, adjust the pH value of the system to 9-10, heat to 50-70° C., introduce nitrogen, add vinyl trimethoxysilane, react for 4-6 hours, filter, wash and dry to obtain vinyl nano calcium carbonate; Step (2): uniformly mixing vinyl nano-calcium carbonate and deionized water, adding methyl methacrylate, methacrylamide and modified tea polyphenols, introducing nitrogen, adding potassium persulfate, reacting at 70-80° C. for 10-12 hours, and obtaining an amino compound after centrifugation, washing and drying; Step (3): uniformly mixing the amino compound and the glutaraldehyde aqueous solution, stirring at 25-35° C. for 12-14 hours, centrifuging, washing, and drying to obtain an aldehyde-containing compound; uniformly mixing chitosan and acetic acid solution to obtain a chitosan solution, adding the aldehyde-containing compound and sodium borohydride, reacting at 20-40° C. for 4-6 hours, centrifuging, washing, and drying to obtain an intermediate; Step (4): the intermediate and isopropanol are mixed evenly, sodium hydroxide solution is added to adjust the pH to 9-10, 2,3-epoxypropyltrimethylammonium chloride is added, and the mixture is reacted at 60-70° C. for 5-7 hours. After precipitation, filtration, washing and drying, modified nano-calcium carbonate is obtained.

2. The method for preparing a transparent polypropylene medical plastic cup according to claim 1, characterized in that: The plastic cup comprises the following components by weight: 60-80 parts of polypropylene, 3-8 parts of polyoxymethylene, 5-15 parts of modified nano calcium carbonate, 3-5 parts of kaolin, 2-4 parts of talcum powder, 0.2-0.4 parts of nucleating agent, 0.5-1.5 parts of lubricant, 1-3 parts of antioxidant and 0.5-1.0 parts of stabilizer.

3. The method for preparing a transparent polypropylene medical plastic cup according to claim 1, characterized in that: In the step (1), the mass ratio of nano-calcium carbonate, anhydrous ethanol, deionized water and vinyltrimethoxysilane is 1:(15-20):(3-5):(2-4).

4. The method for preparing a transparent polypropylene medical plastic cup according to claim 1, characterized in that: In the step (2), the mass ratio of vinyl nano-calcium carbonate, methyl methacrylate, methacrylamide and modified tea polyphenols is 1: (1-2): (2-4): (0.5-1.5).

5. The method for preparing a transparent polypropylene medical plastic cup according to claim 4, characterized in that: The preparation method of the modified tea polyphenols is as follows: The tea polyphenols and ethyl acetate are mixed evenly, maleic anhydride and pyridine are added, and the mixture is reacted in a water bath shaker at 50-70° C. for 5-7 hours. After vacuum rotary evaporation, recrystallization and freeze drying, the modified tea polyphenols are obtained.

6. The method for preparing a transparent polypropylene medical plastic cup according to claim 1, characterized in that: In the step (3), the mass ratio of the amino compound to the glutaraldehyde aqueous solution is 1:(50-100), and the concentration of the glutaraldehyde aqueous solution is 25wt%.

7. The method for preparing a transparent polypropylene medical plastic cup according to claim 1, characterized in that: In the step (4), the mass ratio of the intermediate, isopropanol and 2,3-epoxypropyltrimethylammonium chloride is 1:(15-30):(3-5), and the concentration of the sodium hydroxide solution is 40wt%.

8. The method for preparing a transparent polypropylene medical plastic cup according to claim 2, characterized in that: The lubricant is polyethylene wax.

9. A transparent polypropylene medical plastic cup obtained according to the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Absorbent cotton gauze containing nanometer silver and chitosan, preparation device as well as method thereof

    CN102120043A

  • Chitosan grafted modified peat adsorption material

    CN105032368A

  • Breathable preservation plastic packaging bag

    CN109265868A

  • Tea polyphenol modification method for improving inhibition rate of non-enzymatic glycosylation reaction and application of modified tea polyphenol

    CN112206265A

  • Efficient PP flame-retardant master batch and preparation method thereof

    CN113248831A

Cited By

  • Polypropylene material for logistics turnover and preparation process thereof

    CN120289912A

  • Polypropylene material for logistics turnover and preparation process thereof

    CN120289912B

  • Environment-friendly medicinal composite packaging film and preparation method thereof

    CN120399302A

  • Mildew-proof antibacterial polyolefin material as well as processing technology and application thereof

    CN120484379A

  • Wear-resistant modified polypropylene plastic for turnover box and preparation method of wear-resistant modified polypropylene plastic

    CN121293632A